(untitled) (Konferensiyalar | Conferences, 2024)
This article explores the various ways that music and song influence English language teaching approaches. It explores how incorporating music and song into language instruction improves vocabulary acquisition, grammatical comprehension, cultural awareness, and student engagement. It does this by drawing on a wide range of academic studies and practical views. This article promotes the use of music as a potent instrument for establishing dynamic, immersive, and productive learning environments in English language classrooms by examining various pedagogical techniques and empirical studies.